Relationship Between Knowledge Level And Early Marriage Occurrence - Haerani; Fitriani (Comprehensive Health Care, 2017)
United Nations Children’s Fund (UNICEF) has high cases of early marriage in Indonesia. The figure is 340,000 per year. Meanwhile, 50,000 girls in Indonesia are estimated to get married before the age of 15 years. Young women in Indonesia aged 10-14 years old married in 2010 as much as 0.2%. Even though the proportion is small, this shows that more than 22,000 young women aged 10-14 years in Indonesia are married. This study aims to determine the relationship of the level of knowledge with the incidence of early marriage in Mannaungi Hamlet, Gattareng Village, Gantarang District, Bulukumba Regency. A cross-sectional study design with a population of 50 respondents, a sample size of 22 respondents employing a purposive sampling, a questionnaire research instrument for the level of knowledge and an observation sheet for early marriages. The results of the study using Fisher's exact test (ᵖ = 0.026 <α = 0.05), it was concluded that there was a significant relationship between the level of knowledge and the incidence of early marriage. It is recommended to teens not to rush to get married at an early age.